Economic-statistic Evaluation of the Balances of Payments of the Baltic States - Kalinauskas, Žilvinas (Ekonomika, 2003)
The balance of payments consists of standard items, i. e. accounts. Current account shows bilateral transactions in bade and services, receivable and payable interest, dividends and current transfers. Capital account registers capital transfers and the purchase and sale of non-financial funds and intangible assets by non-residents. Financial account (in Lithuania Capital and Financial accounts are combined together) registers the movement of financial funds from one country to another. Here we can find direct investments, portfolio investments and other investments to and from country. The main part of the balance of payments is changes in the official reserve assets. The goal of this work is to compare items of the balances of payments in three Baltic countries and to evaluate the current account deficit. As well as author introduces with developments of foreign trade indicators in Lithuania. In the first half of 2002 the biggest current account deficit was in Estonia, the smallest one was in Lithuania. Foreign direct investments, portfolio investments and other investments were the main sources of financing of this deficit. The official reserve assets were not as financing source because they increased in all three countries. However, the ratio of the gross foreign debt to GDP in Latvia and Estonia exceeded sustainable bounds. In addition, the ratio of gross foreign debt to exports of goods and services in Latvia was very high. It shows that in the future Latvia and Estonia could have problems related to the repayment of this debt As well as the costs of debt service can increase in these two countries.